2017
DOI: 10.1111/zph.12423
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence for the co‐circulation of two lineages of influenza D viruses in equine populations of the Midwest United States

Abstract: Summary Influenza D virus (IDV) is a newly described influenza type of the Orthomyxoviridae virus family that was first isolated from diseased swine in 2011 and has subsequently been detected in cattle around the world in 2014. In addition, serological evidence for IDV infection in humans has been recently established. Despite all the progress, the full range of susceptible hosts for this novel virus has yet to be determined, but includes swine, bovine, small ruminants and human. This study was designed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 13 publications
1
69
0
3
Order By: Relevance
“…Further epidemiological studies revealed that IDVs circulate in cattle in many countries including the USA (24), Mexico (5), China (6), Japan (7, 8), France (9), Italy (10), Ireland (11), Luxembourg (12), and African countries (13). Furthermore, serological studies showed that IDV antibodies are found in pigs (14), sheep (15, 16), goats (15, 16), dromedary camels (13, 17), horses (18), and humans (19). These findings imply that IDVs are globally distributed in several animal hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Further epidemiological studies revealed that IDVs circulate in cattle in many countries including the USA (24), Mexico (5), China (6), Japan (7, 8), France (9), Italy (10), Ireland (11), Luxembourg (12), and African countries (13). Furthermore, serological studies showed that IDV antibodies are found in pigs (14), sheep (15, 16), goats (15, 16), dromedary camels (13, 17), horses (18), and humans (19). These findings imply that IDVs are globally distributed in several animal hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Two lineages of IDVs are primarily responsible for current IDV global infections (1,3,13). Furthermore, these two distinct lineages of IDVs can also coinfect the same animals (3,19). To develop an IDV vaccine that could prevent infection from both lineages of IDV, we designed and constructed an IDV HEF consensus gene (ConD-HEF)-based vaccine, FluD-Vax.…”
Section: Resultsmentioning
confidence: 99%
“…However, subsequently epidemiological data suggest cattle are the primary reservoir (1,5,7,8). In addition to swine and cattle, IDV infections have been reported in goats, sheep, equines, buffalos, and camels (2,5,9,10). IDV has also been shown to infect ferrets (4) and guinea pigs (11,12) in experimental settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high seroprevalence, cattle is the proposed natural reservoir of IDV, in which IDV causes mild respiratory disease symptoms (11). In addition to cattle, IDV-specific antibodies have been detected in swine, feral swine, equine, ovine, caprine and camelid species, suggesting a broad host tropism for IDV (3, 4, 9, 12, 13). However, the most striking observation is the detection of IDV-directed antibodies among humans with occupational exposure to livestock (14).…”
Section: Introductionmentioning
confidence: 99%